Communication : - Beebe, Steven A. (Pearson, 2013)
Unit i principles of communication -- Foundations of human communication -- Self-awareness and communication -- Understanding verbal messages -- Understanding nonverbal messages -- Listening and responding -- Adapting to others : diversity and communication -- Unit ii interpersonal communication -- Understanding interpersonal communication -- Enhancing relationships -- Unit iii communicating in groups and teams -- Understanding group and team performance -- Enhancing group and team performance -- Unit iv presentational speaking -- Developing your presentation -- Organizing and outlining your presentation -- Delivering your presentation -- Speaking to inform -- Speaking to persuade -- A interviewing -- B sample speeches for discussion and evaluation